ANALISIS KETERAMPILAN BERKOMUNIKASI MAHASISWA CALON GURU IPA DALAM MELAKUKAN MICROTEACHING - Nurwahidah, Indri; Nugraheni, Diah (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
One of the skills that need to be considered in preparing prospective science teachers is communication skills. The purpose of this study was to determine the communication skills of prospective science teacher students in conducting microteaching. The type of research used was descriptive qualitative research, namely by describing the communication skills of prospective science teacher students through the application of basic teaching skills in conducting microteaching. The communication skills observed were basic teaching skills including, 1) questioning skills, 2) explaining skills, 3) using variation skills, 4) providing reinforcement skills, 5) opening and closing lesson skills, 6) group and individual teaching skills, 7) class management skills, and 8) skills in guiding small group discussions. Based on the results of the study, the average value of the first microteaching activity was 80, the average value of the second microteaching was 84, and the average value of the third microteaching was 86. It can be concluded that the average communication skills of prospective science teacher students in conducting microteaching are in the good category.